Effects Of Cymbopogon Sp. Essential Oils And Streptomycin Sulfate On Antimicrobial Proteins Production By Bacillus Subtilis Atcc 21332 - Hairul Shahril Bin Muhamad (Universiti Sains Islam Malaysia, 2015)
Proteins level produced by bacteria may be increased in stressful surroundings, such as in the presence of antimicrobial agent. It appears that many antimicrobial agents, when used at low concentrations, have in common the ability to activate or repress gene transcription, which is distinct from their inhibitory effect. However, there have been comparatively few studies on the potential of natural compounds as a specific chemical signal that can trigger a variety of biological functions. Therefore, the aim of this study is to evaluate the effects of Cymbopogon sp. (which are C. nardus and C. flexuosus) essential oils and Streptomycin Sulfate in regulating proteins or peptides production by Bacillus subtilis ATCC 21332. Results of Microdilution assay showed that the Minimum Inhibition Concentrations (MICs) of C. nardus and C. flexuosus as well as Streptomycin Sulfate on B. subtilis ATCC 21332 were 1.56% (v/v), 0.2% (v/v) and 2.5 mg/ml respectively. C. flexuosus and C. nardus essential oils at concentration of 0.01 MIC, each was added during early log phase of bacterial growth at 37ºC, resulting the production of new intracellular proteins with similar approximate size of 180 kDa in which recognized as DNA-directed RNA polymerase β subunit enzyme and respiratory nitrate reductase α subunit enzyme respectively. Besides, when B. subtilis ATCC 21332 were induced by C. flexuosus essential oil and Streptomycin Sulfate during log phase of growing cells at 30ºC could also secrete the extracellular proteins with approximate size of 30 kDa, identified as Bacillopeptidase F. In addition, B. subtilis ATCC 21332 in the presence of either C. nardus or C. flexuosus essential oils could secrete the bioactive extracellular proteins with potent antimicrobial activity against certain Gram-positive and Gram-negative bacteria. Hence, B. subtilis ATCC 21332 in stressful condition with the presence of either Cymbopogon sp. essential oils or Streptomycin Sulfate at 0.01 MIC level were able to induce the production or secretion of bioactive proteins.